Síntese e caracterização de um cimento a base de hidroxiapatita dopado com óxido de nióbio para uso em procedimentos de regeneração óssea - Farias, Ítalo de Lima (2023)
The use of grafts in bone regeneration procedures is a common clinical practice in dentistry, in order to ensure bone formation to support soft tissues, or to enable reconstructive procedures in the bucomaxillofacial complex. For this purpose, several types of biomaterials can be used, with synthetic hydroxyapatite being an alternative at a reduced price. Characteristics such as biocompatibility, bioactivity and osteoconduction allow its use for this purpose. However, its use in direct clinical procedures is hampered by its low mechanical resistance and low radiopacity. Under this bias, the objective of this study was to develop a cement based on hydroxyapatite and doped with niobium oxide as a radiopacifying material to be used in dental procedures for bone regeneration. For this purpose, hydroxyapatite was synthesized by the wet precipitation method, to which niobium oxide was added and a hydrogel matrix based on carboxymethylcellulose, calcium silicate, glycerin and water. The products were characterized in terms of morphology, physicochemical characteristics by means of X-ray diffraction, infrared spectroscopy with Fourier transform, setting time, workability and fluidity, radiographic analysis, pH and microstructure by scanning electron microscopy. The results showed that it was possible to obtain a cement based on hydroxyapatite and niobium, without changing the initial phases of the reagents, with radiopacity, good workability and fluidity to be used by means of devices such as syringes. In addition, the material presented a basic pH that favors possible antimicrobial activity and cell growth. Morphologically, microscopic analysis revealed a porous microstructure that may allow cell growth and nutrient transport in vivo. The cement obtained showed promising results in order to be applied in surgeries through minimally invasive procedures, being a moldable material indicated for filling irregular bone defects, with the possibility of radiographic clinical follow-up, as well as use in tissue engineering.